Draft Genome Sequence of the Human-Pathogenic Fungus Scedosporium boydii - Duvaux, Ludovic (Genome Announc, 2017)
The opportunistic fungal pathogen Scedosporium boydii is the most common Scedosporium species in French patients with cystic fibrosis. Here we present the first genome report for S. boydii, providing a resource which may enable the elucidation of the pathogenic mechanisms in this species.